2015
DOI: 10.7314/apjcp.2015.16.14.6155
|View full text |Cite
|
Sign up to set email alerts
|

14-bp Insertion/Deletion Polymorphism of the HLA-G gene in Breast Cancer among Women from North Western Iran

Abstract: Background: The human leukocyte antigen-G (HLA-G) gene is highly expressed in cancer pathologies and is one strategy used by tumor cells to escape immune surveillance. A 14-bp insertion/deletion (InDel) polymorphism of the HLA-G gene has been suggested to be associated with HLA-G mRNA stability and the expression of HLA-G. The aim of present study was to assess any genetic association between this polymorphism and breast cancer among Iranian-Azeri women. Materials and Methods: In this study 227 women affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
14
1
1
Order By: Relevance
“…However, in other studies, no associations were found in a group of women from northern Tunisia (Zidi et al, 2016). This was also observed in a South Korean population (Jeong et al, 2014) and Azeri population located in northwestern Iran (Haghi et al, 2015). In the latter study, a significant positive association was found between the del allele and advanced stages of BC (stage I vs stages II and III).…”
Section: Discussionmentioning
confidence: 63%
“…However, in other studies, no associations were found in a group of women from northern Tunisia (Zidi et al, 2016). This was also observed in a South Korean population (Jeong et al, 2014) and Azeri population located in northwestern Iran (Haghi et al, 2015). In the latter study, a significant positive association was found between the del allele and advanced stages of BC (stage I vs stages II and III).…”
Section: Discussionmentioning
confidence: 63%
“…Articles included comprised case-control studies involving the HLA-G 3′UTR 14-bp polymorphism and clinical situations/ diseases. Studies were grouped according to clinical characteristics, pathogenesis and immune response as follow: (1) cancer 2 -B-Cell Lymphoma [27], Breast Cancer [28][29][30][31][32], Cervical Cancer [33][34][35][36], Colorectal cancer [37], Esophageal Cancer [38], Hepatocellular Carcinoma [39][40][41], Head and Neck Squamous-Cell Carcinoma (HNSCC) [42], Lung Cancer [43], Neuroblastoma [44], Papillary Thyroid Cancer [45] and Prostate Cancer [46]; (2) autoimmune diseases 3 -Hashimoto's Thyroiditis [45], Juvenile Idiopathic Arthritis [47], Multiple Sclerosis [48][49][50][51], Non-segmental Vitiligo [52], Pemphigus Vulgaris [53], Rheumatoid Arthritis [47,[54][55][56][57][58], Systemic Lupus Erythematosus (LES) [59][60][61][62][63][64][65][66][67] and Type 1 Diabetes [68]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Expression levels of HLA-G increase in BC,21 which associates with poor prognosis 22. Following studies on a 14 bp InDel polymorphism in the HLA-G gene, Haghi et al performed genotyping and found that patients with higher BC stages had a higher frequency of allele deletion compared with patients with lower stages, indicating that the 14 bp InDel polymorphism in the HLA-G gene was a risk factor for the development of BC 23. In addition, the area under the curve for receiver operating characteristic values of the soluble form of HLA-G (sHLA-G) can help identify metastasis, suggesting that sHLA-G may be utilized as a biomarker for the diagnosis of BC, particularly at the metastasis stage 24.…”
Section: Tumor-related Immune Evasionmentioning
confidence: 99%